2009 15th International Conference on Parallel and Distributed Systems 2009
DOI: 10.1109/icpads.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ConnectX Virtual Protocol Interconnect for Data Centers

Abstract: Abstract-With the emergence of new technologies such asVirtual Protocol Interconnect (VPI) for the modern data center, the separation between commodity networking technology and high-performance interconnects is shrinking. With VPI, a single network adapter on a data center server can easily be configured to use one port to interface with Ethernet traffic and another port to interface with high-bandwidth, low-latency InfiniBand technology. In this paper, we evaluate ConnectX VPI using microbenchmarks as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The performance of SDP and IPoIB in a data center context for reliable connection based SDP and IPoIB has been evaluated by Balaji et al [4], where it was observed that SDP and IPoIB can have a beneficial effect on data center performance. The performance of combined Ethernet/IPoIB/SDP traffic via VPI for ConnectX adapters has been evaluated by Grant et al [7], in which it was shown that multi-port adapters running in IB and Ethernet mode simultaneously can be effective for increasing the performance of back-end data center architectures. All of this previous work differs from this paper in that it never considered unreliable datagrams for either IPoIB or SDP and never examined offload capabilities of InfiniBand network adapters.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The performance of SDP and IPoIB in a data center context for reliable connection based SDP and IPoIB has been evaluated by Balaji et al [4], where it was observed that SDP and IPoIB can have a beneficial effect on data center performance. The performance of combined Ethernet/IPoIB/SDP traffic via VPI for ConnectX adapters has been evaluated by Grant et al [7], in which it was shown that multi-port adapters running in IB and Ethernet mode simultaneously can be effective for increasing the performance of back-end data center architectures. All of this previous work differs from this paper in that it never considered unreliable datagrams for either IPoIB or SDP and never examined offload capabilities of InfiniBand network adapters.…”
Section: Related Workmentioning
confidence: 99%
“…As such, it provides a compromise between offering the feature rich high-speed IB network and the required legacy support for traditional data center applications written for IP-based protocols. This is a critical step towards the goal of converging high-speed networking fabrics and existing enterprise data center networking solutions in a single system, where cost effective Ethernet technologies can be supplemented with high-speed networks in order to increase overall data center performance [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations